2011
DOI: 10.1164/rccm.201011-1928oc
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Chronic Obstructive Pulmonary Disease Is Associated with Female Sex, Maternal Factors, and African American Race in the COPDGene Study

Abstract: Rationale: The characterization of young adults who develop lateonset diseases may augment the detection of novel genes and promote new pathogenic insights. Methods: We analyzed data from 2,500 individuals of African and European ancestry in the COPDGene Study. Subjects with severe, early-onset chronic obstructive pulmonary disease (COPD) (n ¼ 70, age , 55 yr, FEV 1 , 50% predicted) were compared with older subjects with COPD (n ¼ 306, age . 64 yr, FEV 1 , 50% predicted). Measurements and Main Results: Subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
141
4
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(160 citation statements)
references
References 42 publications
7
141
4
3
Order By: Relevance
“…In the vast majority of patients, cigarette smoke is the culprit, highlighting the importance of prevention efforts (1,4). In some cases, even after minimal cigarette smoke exposure, severe emphysema develops at a young age, as early as the fifth decade (5,6). Several pieces of evidence support a genetic etiology for these cases (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the vast majority of patients, cigarette smoke is the culprit, highlighting the importance of prevention efforts (1,4). In some cases, even after minimal cigarette smoke exposure, severe emphysema develops at a young age, as early as the fifth decade (5,6). Several pieces of evidence support a genetic etiology for these cases (7).…”
mentioning
confidence: 99%
“…For example, in addition to severe, young-onset disease, emphysema may cluster in families (5,6). In familial cases, airspace destruction is frequently the predominant phenotype and occurs in the absence of significant airway obstruction, suggesting that emphysema may be a definable heritable trait that is separable from chronic obstructive pulmonary disease (COPD) (5)(6)(7). This article reviews the emerging role of telomerase and telomere abnormalities in driving emphysema susceptibility.…”
mentioning
confidence: 99%
“…5 Although COPD is more frequently observed in males, the number of females with COPD is on the rise. 6,7 Smoking among women has been gradually increasing worldwide. In addition, smoke due to biomass fuel is being recognized as a potential risk factor in the development of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The socioeconomic status may be linked to a child's birth weight. Although controversial, some studies have suggested that women are susceptible to tobacco smoke [10][11][12].…”
Section: Factors Influencing Disease Development and Progressionmentioning
confidence: 99%